Oral contraception in adolescents with type 1 diabetes and its association with cardiovascular risk factors. A multicenter DPV study on 24 011 patients from Germany, Austria or Luxembourg. Issue 5 (27th February 2018) - Bohn, Barbara; Mönkemöller, Kirsten; Hilgard, Dörte; Dost, Axel; Schwab, Karl Otfried; Lilienthal, Eggert; Hammer, Elke; Hake, Kathrin; Fritsch, Maria; Gohlke, Bettina; de Beaufort, Carine; Holl, Reinhard W; et al.
Abstract : Objective: To investigate differences in cardiovascular risk factors and metabolic control in girls with type 1 diabetes with or without use of oral contraceptives (OC) from the multicenter "diabetes prospective follow‐up" (DPV) registry. Methods: Twenty‐four thousand eleven adolescent girls (13 to < 18 years of age) from Germany, Austria or Luxembourg with type 1 diabetes from the DPV registry were included in this cross‐sectional study. Multivariable regression models were applied to compare clinical characteristics (hemoglobin A1c [HbA1C ], blood pressure, serum lipids, body mass index) and lifestyle factors (smoking, physical inactivity, alcohol consumption) between girls with or without OC use. Confounders: age, diabetes duration and migration background. Statistical analysis: SAS 9.4. Results: In girls with type 1 diabetes and OC use, clinical characteristics and lifestyle factors were less favorable compared to non‐users. Differences were most pronounced for the prevalence of dyslipidemia (OC‐users: 40.0% vs non‐users: 29.4; P < .0001) and the number of smokers (OC‐users: 25.9% vs non‐users: 12.5%; P < .0001). OC use, sociodemographic characteristics and lifestyle factors explained between 1 and 7% of the population variance in serum lipids and blood pressure. The use of OC explained a small additional proportion in all variables considered (<1%). Conclusions: OC use in adolescent girls with type 1 diabetes was associated with a poorer cardiovascular risk profile. Biological risk factors were partly explained by a clustering of sociodemographic and lifestyle factors with a small additional contribution of OC use. Prescription of OC should therefore be combined with a screening for cardiovascular risk factors and targeted education.